Half brother - Oppel, Kenneth, 1967- (New York : Scholastic Press, 2010)
In 1973, when a renowned Canadian behavioral psychologist pursues his latest research project-- an experiment to determine whether chimpanzees can acquire advanced language skills-- he brings home a baby chimp named Zan and asks his thirteen-year-old son to treat Zan like a little brother.
012-017.
Keywords: Chimpanzees -- Behavior -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Experiments -- Juvenile fiction; Victoria (B.C.) -- History -- 20th century -- Juvenile fiction; Canada -- History -- 20th century -- Juvenile fiction; Chimpanzees -- Habits and behavior -- Fiction; Human-animal communication -- Fiction; Experiments -- Fiction; Victoria (B.C.) -- History -- 20th century -- Fiction; Canada -- History -- 20th century -- Fiction